Highly active selenium nanotherapeutics combined with metformin to achieve synergistic sensitizing effect on NK cells for osteosarcoma therapy - Du Yanxin; Zhang Zehang; Yang Yu; Liu Ting; Chen Tianfeng; Li Xiaoling (Nanophotonics, 2022)
NK cells-based cancer therapy combined with chemotherapeutic drugs for the treatment of tumors can enhance the immunosensitivity of NK cells, increase the expression of NK cell receptors, and eventually boost the killing effect of NK cells on cancer cells. Selenium (Se) with different chemical structures can be metabolized into selenoproteins to regulate tumor and immune cells’ fate and functions. Herein, we found that, functionalized Se nanoparticles (SeNPs) combining with metformin (met) could amply the immunotherapeutic effects of NK92 cells against osteosarcoma cancer. The results revealed that TW80-SeNPs combined with met had the optimum performance on NK92 cells for HepG2 cells, owing to the increased ROS in HepG2 cells and the augmented expression of cell surface receptor proteins ULBP-3/4, PD-L1, MICA, and NK92 cell surface receptor proteins PD-1 and FasL. Additionally, TW80-SeNPs were gradually metabolized into selenoproteins (Gpx4 and TR1) into human osteosarcoma MG63 cells to reinforce the anticancer effect of NK92 cells by regulating the redox balance in the tumor microenvironment. This study provides a therapeutic approach in treating cancer itself or diabetes coupled with cancer. Moreover, it provides a multidrug strategy to improve immune cell function in practical applications, especially for synergistic immunotherapy of osteosarcoma.